Nanoparticles based on disulfide-containing poly(β-amino ester) and zwitterionic fluorocarbon surfactant as a redox-responsive drug carrier for brain tumor treatment. (4th October 2018) - Feng, Ruoyang; Chen, Qian; Zhou, Ping; Wang, Yinsong; Yan, Hua
Abstract: Malignant brain tumors are often characterized by rapid growth, high invasiveness and poor prognosis. Current methods for brain tumor treatment are dramatically limited because of their inability to cross the blood–brain barrier (BBB) and enter the tumor cells. In this study, we prepared redox-responsive nanoparticles based on disulfide-containing poly( β -amino ester) (ssPBAE) and a zwitterionic fluorocarbon surfactant (Intechem-02) that has a carboxybetaine moiety in molecular structure, and preliminarily evaluated their potential as a drug carrier for brain tumor treatment. These nanoparticles, named as ssPBAEI, had a regular spherical shape and a small size below 50 nm with a relative narrow distribution. Doxorubicin (DOX), as a model chemotherapeutic drug, was efficiently encapsulated into ssPBAEI nanoparticles with a loading content of 25.4%. DOX-loaded ssPBAEI nanoparticles (ssPBAEI/DOX) showed significant redox-responsive in vitro release property and successfully carried DOX across a BBB model, monolayer of human brain capillary endothelial hCMEC/D3 cells. In human glioma LN229 cells, ssPBAEI/DOX nanoparticles were efficiently internalized and DOX was successfully released afterwards, thus significantly inhibited cell growth and induced cell apoptosis. In summary, this nanoparticle system based on ssPBAE and Intechem-02 showed a great potential as a drug carrier for brain tumor treatment.